Growth of Retail in India with Pantaloons as a case study - Saraogi, Paridhi (2006)
This study was conducted to gather a deep insight into the Indian retail market. The market for retail in India has had a history of being extremely fragmented, with 97% of it being formed by the unorganised sector. Organised of modern retail can account for only about 3% of the Indian retail market. But with favourable changes in the environment, all eyes are set on an expected boom in the retail industry, with large domestic players entering the arena and powerful global players looking for a door to enter. Thus a huge growth in the organised retail sector is expected in the next five years.